The Influence of Rainfall and Evaporization Wetting-Drying Cycles on the Slope Stability - Ya Zhao (Advances in Meteorology)
The decay of soil strength and the change of soil infiltration characteristics caused by the dry and wet cycle effect generated by the rainfall-evaporation process are important factors that induce slope instability. How to consider the effect of soil strength decay and water-soil characteristic curve hysteresis effect on transient stability change of slope is the key to solve this problem. In this paper, transient stability analysis of slopes considering soil strength decay and water-soil characteristic curve hysteresis is carried out based on Geo-Studio. The results of the study showed that the change of transient safety factor of the slope caused by rainfall-evaporation dry and wet cycle process has an overall decreasing trend and the safety factor decreased by 43% compared to the initial state. The seepage characteristics of the rainfall-evaporation dry-wet cycle have certain regularity. The location of slope measurement points has a greater influence on the magnitude of the pore pressure change: foot of slope > middle of slope > top of slope. Also, there is a significant response hysteresis in the change of pore pressure with increasing depth at the same location. The rainfall intensity has a certain influence on the change of slope safety factor, but its influence is not obvious when the rainfall intensity exceeds a certain amount.